2017
DOI: 10.1002/ijc.31047
|View full text |Cite
|
Sign up to set email alerts
|

Do pancreatic cancer and chronic pancreatitis share the same genetic risk factors? A PANcreatic Disease ReseArch (PANDoRA) consortium investigation

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a very aggressive tumor with a five-year survival of less than 6%. Chronic pancreatitis (CP), an inflammatory process in of the pancreas, is a strong risk factor for PDAC. Several genetic polymorphisms have been discovered as susceptibility loci for both CP and PDAC. Since CP and PDAC share a consistent number of epidemiologic risk factors, the aim of this study was to investigate whether specific CP risk loci also contribute to PDAC susceptibility. We selected five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In addition, both pancreatic cancer tissue and CP have same dysregulated signaling pathways, such as nuclear factor kappa B, cytokines, peroxisome proliferator-activated receptor-γ, as well as reactive oxygen species [15]. However, there is possibly no identical genetic susceptibility between pancreatic cancer and CP, at least in the variants with high frequency [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both pancreatic cancer tissue and CP have same dysregulated signaling pathways, such as nuclear factor kappa B, cytokines, peroxisome proliferator-activated receptor-γ, as well as reactive oxygen species [15]. However, there is possibly no identical genetic susceptibility between pancreatic cancer and CP, at least in the variants with high frequency [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the processes of genotype accumulation and clonal expansion are required for the development of invasive PDAC (11,16,20). Many efforts have been made to identify gene mutations associated with pancreatic cancer, including mutL homolog 1 and PMS1 homolog 1, mismatch repair system component (21), and BRCA1/2 DNA repair (22).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, biomarkers like Glypican-1, CD63, and miR-451a exosomes seem to be promising [87,88,89]. Nevertheless, in the development of successful biomarkers, it needs to be noted that predispositions such as chronic pancreatitis and pancreatic cancer may have different genetic abnormalities [90]. …”
Section: Procedures Of Screeningmentioning
confidence: 99%